2023
DOI: 10.26508/lsa.202201876
|View full text |Cite
|
Sign up to set email alerts
|

Structural insights into ubiquitin chain cleavage byLegionellaovarian tumor deubiquitinases

Abstract: Although ubiquitin is found only in eukaryotes, several pathogenic bacteria and viruses possess proteins that hinder the host ubiquitin system.Legionella, a gram-negative intracellular bacterium, possesses an ovarian tumor (OTU) family of deubiquitinases (Lot DUBs). Herein, we describe the molecular characteristics of Lot DUBs. We elucidated the structure of the LotA OTU1 domain and revealed that entire Lot DUBs possess a characteristic extended helical lobe that is not found in other OTU-DUBs. The structural … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 87 publications
0
4
0
Order By: Relevance
“…A structure of Wc‐VTD1 confirmed the distinctive VTD‐type DUB fold, revealed structural determinants for ubiquitin binding into the S1 site, and indicated a substrate‐assisted catalysis mechanism underlying the specificity for K6‐linked polyUb (Erven et al , 2022). Interestingly, the specificity of Wc‐VTD1 for K6‐linked polyUb matched the specificity of a VTD family member identified in protists—the natural host of Waddlia —as well as Legionella , which encodes the K6‐linked polyUb‐specific DUB LotA (Kubori et al , 2018; Luo et al , 2022; Kang et al , 2023; Warren et al , 2023). Recently, an additional K6‐linked polyUb‐specific VTD was identified among the ~ 12 DUBs in the Chlamydia ‐like bacterium Simkania negevensis , which also lives inside protist hosts (preprint: Boll et al , 2023).…”
Section: Ubiquitin Hydrolysis By Ca‐clan Deubiquitinasesmentioning
confidence: 82%
See 2 more Smart Citations
“…A structure of Wc‐VTD1 confirmed the distinctive VTD‐type DUB fold, revealed structural determinants for ubiquitin binding into the S1 site, and indicated a substrate‐assisted catalysis mechanism underlying the specificity for K6‐linked polyUb (Erven et al , 2022). Interestingly, the specificity of Wc‐VTD1 for K6‐linked polyUb matched the specificity of a VTD family member identified in protists—the natural host of Waddlia —as well as Legionella , which encodes the K6‐linked polyUb‐specific DUB LotA (Kubori et al , 2018; Luo et al , 2022; Kang et al , 2023; Warren et al , 2023). Recently, an additional K6‐linked polyUb‐specific VTD was identified among the ~ 12 DUBs in the Chlamydia ‐like bacterium Simkania negevensis , which also lives inside protist hosts (preprint: Boll et al , 2023).…”
Section: Ubiquitin Hydrolysis By Ca‐clan Deubiquitinasesmentioning
confidence: 82%
“…A family of related Legionella OTU (LOT) DUBs has recently been identified by sequence homology (Pruneda et al , 2023). The first example, LotA (lpg2248), contains two active OTU‐like domains, the first of which is capable of hydrolyzing K6‐linked polyUb, while the second appears to prefer longer K48‐linked and K63‐linked polyUb chains (Kubori et al , 2018; Luo et al , 2022; Takekawa et al , 2022; Kang et al , 2023; Warren et al , 2023). Interestingly, only the second LotA OTU domain appears to be important for Legionella growth in mouse bone marrow‐derived macrophages, although only in a background where the SidE family ligases are deleted.…”
Section: Ubiquitin Hydrolysis By Ca‐clan Deubiquitinasesmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have identified Lpg0227, Lpg2248, Lpg1621, and Lpg2529 effectors as novel bacterial deubiquitinases, which, due to their primary sequence and structural similarity to eukaryotic ovarian-tumor deubiquitinases (Kang et al , 2023; Kubori et al , 2018; Schubert et al , 2020), have been termed the L egionella OT U-like DUBs (Lot-DUBS). Typically, Lot-DUBs harbor a catalytic triad consisting of Cys-His-Asp residues.…”
Section: Resultsmentioning
confidence: 99%